Sap volatile components in relation to susceptibility of anthracnose and Aspergillus rot of mangoes (Mangifera indica L.) - Krishnapillai, N.; Wijeratnam, R.S.W. (The Journal Of Horticultural Science And Biotechnology, 2017)
Sap burn injury and postharvest diseases are major causes of mango fruit quality deterioration, resulting in considerable postharvest losses in many countries. Susceptibility of selected cultivars of mango in Sri Lanka to sap burn injury and the incidence of anthracnose and Aspergillus rot of mango were examined in this study. Volatile components of non-aqueous (oil) phase were investigated using GC-MS, and artificial inoculation studies were carried out to assess disease resistance with Colletotrichum queesnlandicum (KC 820802) and Aspergillus niger (KC 820801). It was observed that the popular ‘Karuthakolumban’ and ‘Willard’ mangoes with high sap flow at harvest and high sap burn incidence were more susceptible to sap burn injury compared with ‘Chembaddan’ and ‘Ambalavi’ mangoes. Cultivar variations in susceptibility to Aspergillus rot of mangoes are reported for the first time in this study, where ‘Willard’ mangoes were more resistant to Aspergillus rot than other cultivars. The sap exudates of ‘Ambalavi’ and ‘Karuthakolumban’ mangoes were observed to contain the preformed antifungal compounds 5-pentadecyl resorcinol and 5-(Heptadeca-8,11- dienyl) benzene1,3-diol, with variety ‘Ambalavi’ showing a high resorcinol level. These cultivars were found to be resistant to anthracnose disease. These results suggest that presence of sap volatiles is cultivar dependent and could be used to identify cultivars resistant to postharvest diseases and sap burn.
Keywords: Mango sap; postharvest diseases; disease resistance; postharvest disorder